KEABSAHAN PERJANJIAN JUAL BELI ELEKTRONIK MARKETPLACE YANG TIDAK MEMILIKI IZIN BERUSAHA SECARA ELEKTRONIK - Naurah Cyntia Geury Tirasia, (2022)
The times have made the world more sophisticated, agreements that were originally conventional have turned into electronic agreements, such as marketplace agreements. Therefore, the validity of the agreement in the electronic sale and purchase agreement (e commerce) marketplace is made so that there is no loss from the parties. The problem with this research is the validity of the agreement in online buying and selling transactions through an electronic system and the legal consequences that occur if the business actor does not have a business license. This research is a normative juridical research. The research approach in this paper uses the statute approach. In addition, it uses a case approach by analyzing all laws and regulations. Then this study also aims to determine the validity of online buying and selling agreements through electronic systems that do not have a business license and the legal consequences for business actors who do not have a license to do business. The results of this research, firstly, is that the validity of an 2 agreement is declared valid if it fulfills the conditions for the validity of an agreement, namely the existence of an agreement, skills, a certain thing, and a lawful cause must be reflected in the sale and purchase agreement in the electronic marketplace system. The second is the legal consequences of online business actors who do not have a business license, they have a risk to their business and do not get legal protection. Keywords: Legitimacy; Electronic Transactions; Business Licenses